Is Pharmacogenetic Panel Testing Applicable to Low-Dose Methotrexate in Rheumatoid Arthritis? – A Case Report - Jeiziner C; Allemann SS; Hersberger KE; Meyer zu Schwabedissen HE (Dove Medical Press, 2022)
Chiara Jeiziner,1 Samuel S Allemann,1 Kurt E Hersberger,1 Henriette E Meyer zu Schwabedissen2 1Pharmaceutical Care Research Group, Department Pharmaceutical Sciences, University of Basel, Basel, Switzerland; 2Biopharmacy, Department Pharmaceutical Sciences, University of Basel, Basel, SwitzerlandCorrespondence: Chiara Jeiziner, Pharmaceutical Care Research Group, Department Pharmaceutical Sciences, University of Basel, Klingelbergstrasse 50, Basel, 4056, Switzerland, Tel +41 61 207 61 80, Email chiara.jeiziner@unibas.chPurpose: Pharmacogenetic (PGx) panel testing could help to determine the heritable component of a rheumatoid arthritis (RA) patient's susceptibility for therapy failure and/or adverse drug reactions (ADRs) from methotrexate (MTX). Considering the literature mentioning the potential applicability of PGx panel testing within MTX regimens, we discuss the case of a patient who was treated with MTX, suffered from ADRs, and obtained a reactive PGx panel testing.Genotyping: We used a commercial PGx panel test involving the ABC-transporters P-glycoprotein (P-gp; gene: ABCB1), and breast cancer resistance protein (BCRP; gene: ABCG2), the solute carriers reduced folate carrier 1 (RFC1; gene: SLC19A1), and organic anion transporting polypeptide 1B1 (OATP1B1; gene: SLCO1B1), and the enzymes inosine triphosphatase (ITPA), and glutathione transferase P1 (GSTP1). In addition, we genotyped the patient for the enzymes 5-aminoimidazole-4-carboxamide ribonucleotide formyltransferase (AICAR)/inosine monophosphate (IMP) cyclohydrolase (gene name: ATIC), gamma-glutamyl hydrolase (gene name: GGH) and methylenetetrahydrofolate reductase (gene name: MTHFR).Results: The PGx profile of the patient revealed genetic variants in SLC19A1, ABCB1, and MTHFR, which may explain the ADRs experienced during the treatment with MTX and a potentially lower efficacy of MTX. Based on our interpretation of the PGx profile, we recommended the patient to avoid MTX in the future.Conclusion: The MTX pathway is complex, which makes the interpretation of genetic variants affecting metabolism challenging. A reactive PGx panel test was applicable to explain ADRs experienced during MTX treatment for a patient with RA. However, the clinical utility of PGx-guided MTX treatment in a primary care setting is still limited. In order to base a recommendation for MTX on PGx data, we need genome-wide association studies, large prospective multicenter studies and PGx studies, which analyze different multi-gene haplotypes and gene-drug-drug interactions for MTX.Keywords: pharmacogenetics, PGx, ABCB1, SLC19A1, MTHFR, rheumatoid arthritis, methotrexate, MTX